2018
DOI: 10.1002/chem.201804580
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Fluoroalkanes with Mg−Mg Bonds: Scope, sp3C−F/sp2C−F Coupling and Mechanism

Abstract: sp C-F Bonds of fluoroalkanes (7 examples; 1°, 2° and 3°) undergo addition to a low-valent Mg-Mg species generating reactive organomagnesium reagents. Further reactions with a series of electrophiles results in a net C-F to C-B, C-Si, C-Sn or C-C bond transformation (11 examples, diversity). The new reactivity has been exploited in an unprecedented one-pot magnesium-mediated coupling of sp C-F and sp C-F bonds. Calculations suggest that the sp C-F bond activation step occurs by frontside nucleophilic attack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…In contrast, s‐block silyl anions (M‐SiR 3 ; M=Li, Na, K) have been invoked as intermediates in highly efficient methods for the defluorosilylation of sp 2 C−F bonds of fluoroarenes and terminal sp 3 C−F bonds of fluoroalkanes . In related studies we, and others, have shown that main group nucleophiles are exceptional reagents for the C−F functionalisation of fluoroarenes, fluoroalkenes and fluoroalkanes . Strong M—F interactions provide a large thermodynamic driving force for the reaction and can also play a role in determining the selectivity of which C−F bond reacts …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, s‐block silyl anions (M‐SiR 3 ; M=Li, Na, K) have been invoked as intermediates in highly efficient methods for the defluorosilylation of sp 2 C−F bonds of fluoroarenes and terminal sp 3 C−F bonds of fluoroalkanes . In related studies we, and others, have shown that main group nucleophiles are exceptional reagents for the C−F functionalisation of fluoroarenes, fluoroalkenes and fluoroalkanes . Strong M—F interactions provide a large thermodynamic driving force for the reaction and can also play a role in determining the selectivity of which C−F bond reacts …”
Section: Figurementioning
confidence: 99%
“…2a reacts with hexafluoropropene or trifluoropropene but only at high temperature (100 8 8C) over long reaction periods. 2b did not react with hexafluoropropene despite heating for several days at (12),N ÀMgÀN90.04 (10). 2b:M g ÀN2.0040(15) and 2.0615 (16), MgÀ Si 2.6022(9), NÀMgÀN9 1.28 (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,16 Despite this, our group has in recent years demonstrated the C-F activation of simple fluoroalkanes using aluminium and magnesium nucleophiles. 17,18 Furthermore, the groups of Shibata and Martin have both reported C-F activation of a range of fluoroalkanes using group 1 metal silyl nucleophiles. 19,20 We also recently reported the defluorosilylation of industrially relevant hydrofluoroolefins (HFOs) with simple silyl lithium reagents, 21 and in this work we sought to extend the methodology to HFCs.…”
mentioning
confidence: 99%
“…A classical, direct S N 2 attack by 1ÁPMDETA at HCF 3 was calculated to proceed via TS4 (see ESI †) (DG 4 ‡ = 53.8 kcal mol À1 ). A 'frontside S N 2' approach was also considered, as this mechanism has been proposed to operate with highly fluorophilic nucleophiles, 18,33 and the highenergy TS5 (see ESI †) (DG 5 ‡ = 44.7 kcal mol À1 ) was found. We were unable to find a transition state for difluorocarbene formation from PMDETAÁLiCF 3 .…”
mentioning
confidence: 99%